THE EFFECT OF MULTIPLE RENAL ARTERIES GRAFT IN RENAL TRANSPLANTATION (The Research of Medical Science Review, 2025)
OBJECTIVE: The presence of multiple renal arteries (MRA) in kidney grafts is a key concern in transplantation surgery due to the significant increase in vascular and urologic complications. The objective was to assess the incidence of complications in recipients with either a single renal artery or multiple renal arteries on both transplant success and patient survival. METHODS: Following clearance from the ethical review committee, record of 240 patients was reviewed who underwent renal transplantation over a 3-year period. Out of 240, 40 (16.6%) patients had Multiple Renal Arteries graft (MRA). The renal vascular anatomy was identified using computerized tomography (CT) renal arteriography. The occurrence of urological, vascular, and hypertension-related risk factors after the transplant was assessed. Mean creatinine levels of patients were also kept in account. In 26 cases, vascular reconstruction was carried out as a conjoined anastomosis between two arteries of similar size, while in 10 cases, an end-to-side anastomosis was done, connecting smaller arteries to larger ones. In 04 cases multiple anastomoses were performed. Performa was used to collect the data. RESULTS: The study involved 240 patients, 40 patients had graft with multiple renal arteries. There was no significant difference between the two groups in terms of donor age or the cause of renal failure (p = 0.841 and 0.343). The most common causes of renal failure were idiopathic renal failure and diabetes mellitus. A strong correlation was found between the occurrence of complications in both groups (p = 0.001). Patients with multiple renal arteries had more urinary (p = 0.24) and vascular complications than those with a single artery, although the difference was only statistically significant for bleeding disorders (p = 0.033). The results indicated that vascular complications were notably higher in recipients with multiple renal arteries, though the difference between the groups was not statistically significant (p = 0.197). CONCLUSION: Our study showed that multiple renal arteries did not negatively impact postoperative urologic or vascular complications, kidney allograft survival, or patient survival when compared to cases with a single renal artery. Therefore, kidney transplantation can be done successfully while using grafts with multiple renal arteries.